The health care training handbook - Wall, Kathryn S.; Wall, Kathryn ([S.l.] : Jossey-Bass, 2000)
The Health Care Training Handbook is a comprehensive tool kit that includes a wealth of information, illustrative clinical and non-clinical examples, tools, and skill building lessons specifically targeted for trainers working in today's health care environment. This essential book covers a broad range of topics such as how to design and implement successful training programs, conduct effective needs assessments, develop management and leadership skills, evaluate results, and track trends in the rapidly changing health care industry.
Keywords: medicine,medical training, handbook,manuals